Identifying dimensions, components and indicators of school-centered management on Islamic-Iranian values - Masoud Taghiani; masoumeh oladiyan; Mahmoud Safari (Institute of Management fekrenoandish, 2023)
Abstract The aim of the current research is to identify the dimensions, components and indicators of school-centered management on Islamic-Iranian values. The research method is practical in terms of purpose, and qualitative in terms of implementation, and descriptive type and thematic analysis. The statistical population of this research includes 19 university professors in the academic year of 2021-2022 in addition to experienced officials of the Education and Training. Sampling method in this research was non-random, purposed for selection of the interviewees, and based on the entrance criteria in the research. Data analysis was done using MAXQDA software. According to the analysis that was carried out using thematic analysis method to determine the dimensions, components and indicators of school-centered management on Islamic-Iranian values, 3 dimensions, 9 components, and 67 indicators were identified and confirmed. The dimensions of school-based management include the individual dimension (mental states, communication, and knowledge development), educational dimension (management skills, educational atmosphere, and informal program), and managerial dimension (professional management knowledge, professional attitude, professional skill). Also, the results showed that school-based management had a favorable situation in all the indicators mentioned in the evaluation. Extended abstract Introduction In today's world, it is certain that for fundamental changes in an organization, managers of organizations must become effective leaders because leadership has significant capacities to create change; leadership includes a wide range of methods to maximize the potential of human capital to achieve Organizational goals which can be called organizational success. Leadership is considered very important because the success or failure of any organization is attributed to the leadership style of the person or group of people who direct the activities of the organization (Kuroda, 2022). Schools are not exempted from this rule, because they are small organizations in a subset of the big institution of education. Therefore, special attention should be paid to various factors such as leadership, management, teacher and student, etc. The philosophy of education, which is an important part of educational sciences and is mainly theoretical and philosophical, has a long history and has undergone various changes since a long time ago. On the other hand, familiarity with ancient and contemporary philosophical ideas of education and training, their review, analysis and criticism is essential for an education thinker and trainer; because it can be a prelude to formulating an education system based on the ideology of school management based on school-centered management and reaching an empowering school (Ishida & Okitsu, 2022).Achieving excellence in schools requires strong school-centered management. This type of management, by providing educational decision-making areas in the school, can effectively use the limited resources of the school and strengthen local participation in the administration of affairs, and people can use more of their energy to improve and develop the school and finally their society and cause innovation and creativity in its performance.In school-oriented management, which has participatory decision-making and its main goal is to improve school performance and improve educational quality in order to improve students' education, the following results will be achieved (Ulfatin et al, 2022).Therefore, the researcher asked the main question: what are the dimensions, components and indicators of school-centered management on Islamic-Iranian values?  Theoretical Framework School-centered management means the restructuring of the education system in order to increase flexibility, lack of concentration and delegation of authority to schools, in such a way that by bringing the place of decision-making closer to the place of its implementation and making decisions in a group manner and seeking participation by those who have the most information about the needs of the school and the conditions governing it and are more affected by the results of education than anyone else (including parents, students, teachers, staff members, interest groups of the society, including industrial owners, National Organization, etc.) and causes the independence, responsibility and accountability of the school to increase, as well as to improve the quality and effectiveness of education (Noruznezhad et al, 2019). Calliba (2022) conducted a research titled self-efficacy, working conditions, school-oriented management practices and teachers' performance. The results of the research showed that school-based management methods affect self-efficacy, improving teachers' working conditions, and ultimately teachers' performance. Barrera et al, (2022) conducted a research titled structural equation model of school-oriented management practices and teachers' commitment in secondary schools. The results of the study showed that the implementation level of school-based management, according to the categories of leadership and governance, curriculum and learning, accountability and continuous improvement, and resource management, is fully implemented in public secondary schools of the sector. Research Methodology This research is applicable in terms of purpose, qualitative in terms of data collection method, and thematic analysis research in terms of research implementation. The statistical population of the research includes 19 people in two groups: a) university professors in 2021-2022 b) officials with experience in education. Sampling method in this non-random, purposeful research was used to select the interviewees based on the entrance criteria. After analyzing the interviews, a total of 3 dimensions, 9 components and 67 indicators were identified in line with the research objectives. Research findings Data analysis was done using MAXQDA software. Based on the obtained results and according to the qualitative analysis, a total of 3 dimensions, 9 components and 67 indicators have been identified and confirmed. It includes individual (mental states, communication, knowledge development), educational (management skills, educational atmosphere, informal program), and managerial (professional knowledge of management, professional attitude, professional skills). School-based management had a favorable situation in all the indicators mentioned in the evaluation. In this research, a model was drawn based on theoretical foundations, opinions of experts, and the statistical community, which had good validity. Conclusion The current research was conducted with the aim of identifying the dimensions, components and indicators of school-centered management on Islamic-Iranian values. The results of this research are in agreement with the results of Ghoraishi & Lashgari (2022), Torani & Hoseinpour (2020), Afista & Bakar (2021), Shibuya (2020), Legistia (2019), Koc & Bastas (2019), Askari & Abdollahi (2020). Regarding this finding, Ghoraishi & Lashgari (2022) showed that school-centered management has been mainly used in interaction with the concepts of "school-centered management, decentralization, management, leadership, school autonomy, responsibility, school principal, participation, school governance, teachers". According to the results obtained in three dimensions, the following suggestions are presented: Individual dimension: hiring and employing managers who are patient, ethical, professional and self-efficient. Strengthening interpersonal communication based on Iranian Islamic values ​​by using religious and ritual ceremonies held in the school. Flexibility in behavior based on Iranian Islamic values ​​and assessment of this flexibility by education inspectors. Creating opportunities for growth based on Iranian Islamic values ​​by using outsourcing mechanisms and using prominent professors based on students' needs for changes. Educational dimension: creating educational and training situations based on Iranian Islamic values ​​by using scientific and cultural events and supporting them in school. Creating a competitive atmosphere based on Iranian Islamic values ​​among students by holding healthy competitions in order to empower students.